Upregulation of ubiquitin-conjugating enzyme E2T (UBE2T) predicts poor prognosis and promotes hepatocellular carcinoma progression. Issue 1 (1st January 2021) - Ren, Xiaoyue; Li, Alex; Ying, Edward; Fang, Jhin; Li, Mingzhu; Yu, Jiao
ABSTRACT: Reportedly, ubiquitin-conjugating enzyme E2T (UBE2T) is closely related to the progression of several malignancies. This work is aimed to probe the role of UBE2T in the progression of hepatocellular carcinoma (HCC) patients. The microarray analysis was executed to screen the differentially expressed genes (DEGs) in HCC tissues. The Cancer Genome Atlas (TCGA) and Gene Expression Profiling Interactive Analysis (GEPIA2) databases, PCR and immunohistochemistry were utilized to validate the dysregulation of UBE2T in HCC. Kaplan-Meier analysis was employed to determine the relationship between UBE2T expression and the prognosis of HCC patients. PCR was carried out to detect UBE2T protein expression in HCC cell lines. Cell Counting Kit-8 (CCK-8) assay and 5-bromo-2ʹ-deoxyuridine (BrdU) experiments were conducted to examine the proliferation of HCC cells. Scratch healing and Transwell experiments were conducted to examine the migration of HCC cells. Bioinformatics analysis and dual-luciferase reporter gene experiments predicted and validated the targeting relationship with miR-212-5p and UBE2T. We found that UBE2T expression was remarkably up-modulated in HCC tissues and cell lines, and its high expression was linked to a worse prognosis in HCC patients. UBE2T overexpression enhanced HCC cell proliferation and migration. Additionally, UBE2T was verified as a downstream target of miR-212-5p. In conclusion, UBE2T overexpression is markedly linked to unfavorable prognosis in HCC patients. UBE2T, regulated by miR-212-5p, significantly enhances the malignant phenotypes of HCC cells, which can be used as a target for HCC diagnosis and prognosis. Graphical abstract: uf0001